Dukungan Sosial dan Kecerdasan Emosional (Emotional Quotient) dengan Stres di tengah Pandemi Covid-19 pada Masyarakat Cempaka Putih Barat, Jakarta Pusat - R. Sibua, Rima Utari; J. Silaen, Sondang Maria (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study is a quantitative study that aims to determine the relationship between social support and emotional quotient with stress amid the Covid-19 pandemic in the Cempaka Putih West Central Jakarta community. The subjects of this study were 110 young adults who lived in West Cempaka Putih with an age range of 20-40 years, using a multistage random sampling technique. This study uses three measurement scales, namely the Stress Scale, Social Provisions Scale (SPS), and Wang and Law Emotional Intelligence Scale (WLEIS). The results showed that there was a significant negative relationship between social support and stress of r = -0.309 and p = 0.001 (p <0.05). There is a significant negative relationship between emotional quotient and stress of r = -0.446 and p = 0.000 (p <0.05). Furthermore, the results of data analysis using multivariate correlation using the SPSS (Statistical Product and Service Solution) version 25.0 for MAC-windows computer program obtained a correlation coefficient of R = 0.507. The research results conclude that the higher social support, the lower stress is felt, then if the higher emotional intelligence, the lower stress is felt, and vice versa, the lower social support, the higher stress is felt. Social support contributed 25.7% more dominantly than emotional intelligence which accounted for 19.9% and the remaining 53% was another factor not examined in this study.